PENGARUH KARAKTERISTIK CEO, CEO OVERCONFIDENCE, DAN BLOCKHOLDER OWNERSHIP TERHADAP KEPATUHAN PAJAK - Fahira, Anggia; Hasnawati; Hervina (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
The low level of tax compliance that occurs in Indonesia causes a lot of losses to the State. The low level of tax compliance requires a reliable understanding of the field. This research explains several problem formulations, including whether CEO characteristics influence tax compliance, whether CEO overconfidence influences tax compliance, and finally whether blockholder ownership influences tax compliance. The population used in this study uses companies listed on the Kompas 100 index on the Indonesian Stock Exchange. Researchers took samples using purposive sampling method with a total of 156 samples. Then, for the analysis used is multiple regression analysis. The results obtained in this research are that CEO education on CEO characteristics has a positive effect on tax compliance, CEO compensation on CEO characteristics has no positive effect on tax compliance, CEO overconfidence has a negative effect on tax compliance. blockholder ownership has no positive effect on tax compliance.